2007
DOI: 10.1002/hed.20713
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of resectable subset after induction chemotherapy in patients with locally advanced head and neck cancer

Abstract: The potential benefit of neoadjuvant chemotherapy with surgery in patients with locally advanced head and neck cancers merits further evaluation in future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Response to induction chemotherapy is widely reported as a prognosticator in head and neck SCC and sinonasal malignancies . Pathological CR to chemotherapy, in particular, has been associated with excellent survival .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Response to induction chemotherapy is widely reported as a prognosticator in head and neck SCC and sinonasal malignancies . Pathological CR to chemotherapy, in particular, has been associated with excellent survival .…”
Section: Discussionmentioning
confidence: 99%
“…It remains debated whether patients who respond to chemotherapy should proceed to surgery or radiotherapy. Some investigators propose using the response to induction chemotherapy as a selection strategy for chemoradiation, whereas others have reported improved survival in patients who receive surgery . It is unclear whether it is necessary to resect all anatomic sites involved by a tumor before induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was used to improve local control rate, decrease distant metastasis rate, and thus improved the OS rate. PF (Cisplatin and continuous infusion of 5-fluorouracil (5-FU) )had been established as the standard induction regimen for advanced cases [4][5][6][7]. Previous studies of preoperative chemotherapy with PF combination regime showed encouraging results in patients with advanced head and neck carcinoma: even though the overall survival was not improved [7,[10][11][12]] , IC achieved high major response (clinical complete or partial response) rate (approximately 48% , range 15%-82%) [7,10,11], with no significant increase in postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, concomitant chemotherapy added to postoperative radiotherapy may improve local-regional control in patients with oral cavity cancers possessing high-risk features [1][2][3]. Two published meta-analyses [4][5][6] concluded that chemotherapy was associated with a small advantage in survival (4% to 6%) in advanced head and neck cancer. While, Licitra et al [7] reported a randomized controlled trial of IC (3 cycles of cisplatin and fluorouracil) for resectable oral cavity cancer (98 patients in the treatment group and 97 patients in the control group), and there was no evidence of improved survival for both arm (5-year overall survival 55%).…”
Section: Introductionmentioning
confidence: 99%